Influence of Auxins on Glucosinolate Biosynthesis in Hairy Root Cultures of Broccoli (Brassica oleracea var. italica) - Hoon Kim, Haeng; Yeon Kwon, Do; Bae, Hanhong; Kim, Sun-Ju; Bok Kim, Yeon; Romij Uddin, MD.; Un Park, Sang (Asian Journal of Chemistry, 2013)
One of the most significant health benefits of cruciferous vegetables results from the presence of biologically active compounds, glucosinolates. Broccoli (Brassica oleracea var. italica) is a nutritionally important crop grown all over the world. The primary purpose of this study was to evaluate the effect of auxins on glucosinolate biosynthesis in the hairy root of broccoli. Eight different glucosinolates, including glucoraphanin, gluconapin, 4-hydroxyglucobrassicin, glucoerucin, glucobrassicin, 4-methoxyglucobrassicin, gluconasturtiin and neoglucobrassicin, were identified by analysis of broccoli hairy root cultures. Low concentration of auxins (0.1 mg/ L) resulted in the highest accumulation of glucosinolates. Treatment with higher concentrations resulted less accumulation of glucosinolates than treatment with 0.1 mg/L of auxins. Among the tested compounds, treatment with 1 mg/L NAA resulted in the lowest accumulation of glucosinolates. Treatment with 0.1 mg/L IAA resulted in the accumulation of 2.2 times more glucosinolates than treatment with 1 mg/L NAA and 1.6 times more glucosinolates than was found in control. Treatment with 0.1 mg/L IBA resulted in the second highest accumulation of glucosinolates. Our results suggest that auxin treatment, especially IAA at a concentration of 0.1 mg/L could be used to mass produce glucosinolates from hairy root culture of broccoli.